Modification of Cyclone Separator Based on IOT Arduino Microcontroller with Activated Carbon from Cocoa Shell Waste as a Tool for Controlling Air Pollution - Thoriq; Hendra Sahputra Ginting, Muhammad; Fiki Agustianda; Fauziah Khairunnisa; Izharul Haq; Siregar, Afrylian Fauzan; Nasution, Juan Akmal (Talenta Publisher, 2024)
Air pollution is the condition of air that is contaminated by the presence of materials, substances or polluting components. One of the causes of air pollution is the combustion or inseneration process because the residue of the process can be released into the air. Based on ISPU, there are five main pollutants, namely: carbon monoxide (CO), sulfur dioxide (SO2), nitrogen oxides (NOX), surface ozone (O3), and dust particles (PM10). This study was conducted to reduce the emission of gases. The use of modified cyclone with adsorbent pipe tube from cocoa husk can increase the efficiency of combustion results with adsorption pipe tube modified cyclone. From the results of the study it was found that emissions from incineration can be controlled with APPU in the form of a cyclone. The use of cyclone alone can reduce NOX and CO levels with a reduction in NOX emissions to 53% and CO to 96%. Both emission reductions are in line with the quality standards. However, the use of adsorption pipe tubes showed better efficiency and effectiveness.